External evaluation in the municipal network of Florianópolis: amendment of teaching work by capital work - de Lima, Thiago Salgado Vaz (2019)
This article analyzes the implications for the teaching work coming from the policy of external evaluation in the Municipal Network of Education of Florianópolis (RME) due to its financing by the Inter-American Development Bank (BID), from 2012. A network of relations is presented to from the contracting of the Center for Public Policies and Education Evaluation of the Federal University of Juiz de Fora (CAEd / UFJF) to formulate, analyze and devolve the results of the evaluation; the active participation of its formulators in the State apparatus; his performances in private organizations are articulated with fractions of capital, clarifying the bourgeois class character of this policy. As a consequence of this logic, it is evident that the recommendations expressed to the work of the teacher of the network are presented as a pretended humanized way to hold, intensify and control the teaching work in line with the current movement of capitalism.